Managing your information using Evernote : gather, organize, archive and share your information (Que, 2015)
"In these video lessons, viewers learn different methods for efficiently creating and managing various types of Evernote content, as well as strategies for keeping Evernote data secure and private. This video course also includes more advanced information to help users customize and utilize this software (or app) in their personal and/or professional lives. This includes an emphasis on advanced uses for the Premium and Business versions of Evernote. In addition to demonstrating specifically how to use each important feature and function of Evernote, this course explains how to sync Evernote information between computers and mobile devices, collaborate on the creation of content with others, share Evernote content with others, back up Evernote content to a cloud-based file sharing service, and customize the application using third-party add-ons."--Resource description page.